Towards incentivising integration: A typology of payments for integrated care - Stokes, J; Struckmann, V; Kristensen, S; Fuchs, S; van Ginneken, E; Tsiachristas, A; van Mölken, M; Sutton, M (Elsevier, 2018)
Traditional provider payment mechanisms may not create appropriate incentives for integrating care. Alternative payment mechanisms, such as bundled payments, have been introduced without uniform definitions, and existing payment typologies are not suitable for describing them. We use a systematic review combined with example integrated care programmes identified from practice in the Horizon2020 SELFIE project to inform a new typology of payment mechanisms for integrated care. The typology describes payments in terms of the scope of payment (Target population, Time, Sectors), the participation of providers (Provider coverage, Financial pooling/sharing), and the single provider/patient involvement (Income, Multiple disease/needs focus, and Quality measurement). There is a gap between rhetoric on the need for new payment mechanisms and those implemented in practice. Current payments for integrated care are mostly sector- and disease-specific, with questionable impact on those with the most need for integrated care. The typology provides a basis to improve financial incentives supporting more effective and efficient integrated care systems.